Using Grammarly Software to Check the Problems in Essay Writing: EFL Pre-service Teachers’ Perceptions - Wulandari, Sintya; Laeli, Anita; Astutik, Indri (New Language Dimensions, 2024)
This research aims to investigate pre-service teachers' perceptions of using Grammarly software to help them check their essays' problems. The study considers the widespread use of AI in English language learning, particularly in writing. The research method used in this paper was a quantitative survey. The instrument used was a questionnaire. 36 English Pre-service teachers from two state universities and one private university in Jember were involved in this study. The findings show a positive response based on five aspects of perception: belief, knowledge, feeling, interest, and motivation. Based on the data, 18-24 participants agree, and 2-12 participants strongly agree with the statement. This data means that more than half of the respondents positively perceive using Grammarly software in essay writing. The belief aspect is the highest frequency (65.3% of respondents agree). This data means that students mostly believe that using Grammarly can help them improve their writing skills and solve their writing problems. On the other hand, the motivation aspect received the lowest response, with less than half (48.6%) agreeing. Therefore, this study recommends that English language education programs emphasize the importance of AI in learning, particularly Grammarly.